2019
DOI: 10.1371/journal.pbio.2006619
|View full text |Cite
|
Sign up to set email alerts
|

Chemosensory sensilla of the Drosophila wing express a candidate ionotropic pheromone receptor

Abstract: The Drosophila wing was proposed to be a taste organ more than 35 years ago, but there has been remarkably little study of its role in chemoreception. We carry out a differential RNA-seq analysis of a row of sensilla on the anterior wing margin and find expression of many genes associated with pheromone and chemical perception. To ask whether these sensilla might receive pheromonal input, we devised a dye-transfer paradigm and found that large, hydrophobic molecules comparable to pheromo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 83 publications
4
37
0
Order By: Relevance
“…Baseline sleep was also increased when Ir52a-GAL4 and Ir76b-GAL4 neurons were simultaneously silenced in the absence of wing cut. A recent study has shown that hydrophobic molecules can be transferred from one fly to the wing margin of another to influence male and female sexual behavior via Ir52a (34). These data support a role for Ir52a in sleep regulation given the interaction between sleep and sexual behavior (21).…”
Section: Specific Wing Chemosensory Neurons Mediate Wing Cut-induced mentioning
confidence: 65%
“…Baseline sleep was also increased when Ir52a-GAL4 and Ir76b-GAL4 neurons were simultaneously silenced in the absence of wing cut. A recent study has shown that hydrophobic molecules can be transferred from one fly to the wing margin of another to influence male and female sexual behavior via Ir52a (34). These data support a role for Ir52a in sleep regulation given the interaction between sleep and sexual behavior (21).…”
Section: Specific Wing Chemosensory Neurons Mediate Wing Cut-induced mentioning
confidence: 65%
“…Insects have evolved a complex peripheral taste system and possess taste sensory neurons in multiple organs including the legs, wings, and labellum (the distal segment of the proboscis) (Scott, 2018). These external taste neurons enable insects to rapidly sample different substrates as they navigate an environment, and insects use taste cues to guide ongoing behaviors including feeding as well as locomotion, egg-laying, grooming, and courtship (Corfas et al, 2019;He et al, 2019;Joseph and Heberlein, 2012;Thistle et al, 2012;Thoma et al, 2016;Yanagawa et al, 2014). Thus the presence of ON and OFF responses to tastants may be important for the generation of behavior in insects.…”
Section: Introductionmentioning
confidence: 99%
“…In insects, GRs expressed in gustatory neurons acts as taste receptors, which are responsible for feeding behaviors (Dunipace et al, 2001;Scott et al, 2001). As a large and highly divergent family of ionotropic glutamate receptors in Drosophila, IRs are subdivided into "antennal IRs, " which are expressed in antennae specifically and mainly involved in olfactory recognition; and "divergent IRs, " which are found in various tissues taking responsible for sensation of taste (Jaeger et al, 2018;Lee et al, 2018;He et al, 2019;Rimal et al, 2019). Various chemosensory associated proteins in insect play diverse functions, such as those listed in Table 1.…”
Section: Introductionmentioning
confidence: 99%